Experimental energetic and exergetic analysis with the novel emulsion fuels incorporating CNT and Al2O3 nano additive for DICI engine - Rai R.K.; Sahoo R.R. (My University, 2025)
Experimental investigation on the energy, sustainability, and exergy based analysis have been performed for the 5% water in diesel emulsion (WiDE) fuel, 50 ppm carbon nanotube (CNT) and 50 ppm aluminium oxide (Al2O3) nano-additive fuels on the diesel engine with changeable engine speed and load in the present study. Analysis revealed that the parameters brake thermal efficiency (BTE), exergy efficiency, exergy destruction rate, engine sustainability, and other exergy parameters have higher values with increasing engine load and engine speed for all fuel samples. The engine BTE and exergy efficiency with 5%WiDE, 5%WiDE-Al2O3 and 5%WiDE-CNT nano additives are found to be 1.49%, 2.7%, and 3.07% and 1.85%, 3.08%, and 5.21% higher, respectively, than diesel fuel at 5.6 kW effective power and 1,500 rpm engine speed. The exergy-based sustainability is found highest for 5%WiDE-CNT fuel, at 2,000 engine rpm with full engine load. The exergy destruction rate and the entropy generation rate with the neat diesel is 1.42% higher than 5%WiDE fuel, while with 5%WiDE-Al2O3 and 5%WiDE-CNT nano additive fuels have 2.07% and 4.15%, higher values, respectively, compared to diesel fuel. © 2021 Inderscience Enterprises Ltd.. All rights reserved.